Diagnostic accuracy of fine-needle aspiration cytology in diagnosis of thyroid nodules - Damle, Gopal Krishna; Daharwal, Ajit Vikram (International Journal of Research in Medical Sciences, 2016)
Background: Thyroid nodules are a common clinical problem Epidemiologic studies have shown the prevalence of palpable thyroid nodules to be approximately 5% in women and 1% in men living in iodine- sufficient parts of the world. The prevalence of thyroid nodules ranges from 4% to 10% in the general adult population and from 0.2% to 1.2% in children. Currently, many investigations including diagnostic imaging studies, serologic and cytogenetic tests as well as histopathological techniques are available to evaluate to evaluate thyroid nodules out. Of all these investigations, fine needle aspiration cytology (FNAC) has become the diagnostic tool of choice for the initial evaluation of solitary thyroid nodule. Methods: A present prospective study was conducted in department of ENT, Dr. BRAM hospital, Pt. JNM Medical College, Raipur, Chhattisgarh, India during study period November 2011 to October 2012. Patients with thyroid nodule were selected for the study. After taking a detailed clinical history, all cases were underwent a thorough ENT and head and neck examination. The clinical findings were recorded. Thyroid function tests and other necessary investigations were also done. Then the patients were referred for fine needle aspiration cytology to the department of Pathology. Depending on the nature of the lesion, decision had taken regarding need for surgery and the extent of surgery. All fine needle aspiration cytology (FNAC) reports were correlated with histopathology diagnosis. Results: Male and female ratio was 1:3.5. Preoperatively FNAC done in 54 cases out of which 36 (66.66%) results were goiter followed by 4 (7.40%) hurthle cell thyroiditis and 2 (3.87%) chronic thyroditis Among 54 cases 1.85% results were follicular neoplasia followed by 3 (5.55%). Fine needle aspiration cytology was 87.5% sensitive in detection of neoplastic lesion and 95.65% sensation of neoplastic lesion and 95.65% specific. Accuracy was 94.44%. Conclusions: Fine needle aspiration cytology is a simple, rapid, inexpensive, well tolerated and harmless method of evaluation mass lesions of the neck especially when there is a close cooperation between the clinician and cytopathologist.